2004
DOI: 10.1211/0022357023051
|View full text |Cite
|
Sign up to set email alerts
|

Acute nephrotoxicity of aristolochic acids in mice

Abstract: Aristolochic acids (AA), present in Aristolochia plants, are the toxin responsible for Chinese herbs nephropathy (CHN), a rapidly progressive tubulointerstitial nephritis (TIN). To clarify the mechanisms of the development of CHN, we tried to induce TIN in mice using AA. Three strains of inbred mice, BALB/c, C3H/He and C57BL/6, received 2.5 mg kg(-1) of AA or AA sodium salt (AANa) daily by intraperitoneal or oral administration, 5 days a week for 2 weeks. Serum and renal tissue were obtained at sacrifice. Twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
81
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 26 publications
10
81
1
Order By: Relevance
“…Our results are generally consistent with those of an earlier study using several strains of mice in which AA-I and AA-II were administered i.p. (Sato et al, 2004). These authors reported focal mild interstitial changes in mice treated with AA-II (Sato et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our results are generally consistent with those of an earlier study using several strains of mice in which AA-I and AA-II were administered i.p. (Sato et al, 2004). These authors reported focal mild interstitial changes in mice treated with AA-II (Sato et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…AA occurs naturally as a mixture of the structural analogs AA-I and AA-II. To explore the relative nephrotoxic and genotoxic potentials of AA-I or AA-II, we used a mouse model developed by Sato et al (2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-3,10 -13 In animals and humans with acute AAN, progressive TEC death with patchy necrosis, primarily affecting proximal TECs in the renal cortex, is the major pathologic feature. 3,10,11,14,15,23 Increased apoptosis has been observed in AA-associated cancers 24 -26 and in cultured tubular cells exposed to AA. 19,27,28 A calcium-dependent mitochondria stress mechanism has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Magnifications: ϫ200 in A through D; ϫ400 in E through F. sis and inflammation in experimental models and patients with acute AAN. 10,14,15 Although apoptosis is an important pathologic feature in in vivo and in vitro studies of acute AAN, 16 -18 the underlying mechanisms remain unclear.…”
mentioning
confidence: 99%